DETERMINANT FACTORS OF INDONESIAN MILLENNIALS’ REVISIT INTENTION: A CASE OF LABUAN BAJO - Farida Komalasari; Eko Ganiarto (FIRM Journal of Management Studies, 2019)
In an effort to increase the number of foreign tourists to Indonesia, the government has set Labuan Bajo as one of the four priority tourist destinations, in addition to Lake Toba, Borobudur and Mandalika. Of the four priority areas, Labuan Bajo is the region with the least number of tourist visits, even though Labuan Bajo has its own uniqueness with its Komodo (giant lizard). Therefore a study of the determinants of revisit to Labuan Bajo, especially for millennial groups, is needed. The main purpose of this study is to determine the determinants factors of the revisit intention of the Indonesian millenials to Labuan Bajo. This research is a quantitative study by interviewing 155 respondents of millennial visitors to Labuan Bajo, who were selected by snowball sampling. The research data was processed and analyzed using the SEM (Stuctural Equation Model) model. The results of the study show that new experiences, new knowledge (push factors), historical values, local values and travelling values (pull factors) influence the destination satisfaction. Furthermore, the destination satisfaction affected the revisit intention to Labuan Bajo.Keywords: push factors, pull factors, tourist satisfaction, revisit intention, Labuan Bajo